In-Situ Measurement of Clipless Cycling Pedal Floating Angles - Champoux, Y.; Pare, D.; Drouet, J.-M.; Rancourt, D. (The Engineering of sport 7, Volume 1, 2008)
In cycling sports, clipless pedals are used by athletes and dedicated cyclists to attach the shoe to the pedal because this allows efficient energy transfer to the bike. Most clipless pedals now offer a degree of freedom (float) to the shoe around an axis normal to the pedal surface. This feature was originally introduced in an attempt to reduce knee injuries due to overuse. Most studies reporting on the influence of the clipless pedal floating angle on knee injuries have been carried out under laboratory conditions and little is known about the use of the float in real road conditions. This paper is an evaluation of the design and accuracy of a new apparatus that can measure the in-situ clipless cycling pedal floating angle. A high-sensitivity sensor that can measure magnetic field orientation is embedded in a commercial pedal. Small magnets temporarily clipped onto the cleat create the required magnetic field around the sensor. This measurement technology eliminates the need for a physical connection between the sensor and the shoe, thus allowing the pedal to be used normally. Static calibration and a subsequent accuracy check revealed that the angle measurement uncertainty was found to be within a range of ±0.25° with an hysteresis of less than 1% Full Scale. Typical in-situ sample floating angle measurements are included to demonstrate the ability of the Instrument to provide useful information. Keywords: Measurement, clipless pedals, floating angle, cycling.